Analysis of ignition temperature range and surrogate fuel requirements for GCI engine. (15th March 2022) - Khaled, Fethi; Javed, Tamour; Farooq, Aamir; Badra, Jihad
Highlights: The temperature ranges relevant to ignition in GCI engines were determined. Fuels with different sensitivities were investigated. The relevant temperature range are within 750–1000 K. Ignition surrogate requirements of fuels inside GCI engine were identified. For low sensitivity GCI fuels, PRF surrogates are good enough auto-ignition surrogates. For high sensitivity GCI fuels, TPRF and TPRFE ignition surrogates are needed. Abstract: Gasoline compression ignition (GCI) technology aims to improve internal combustion engine (ICE) efficiency. However, much is still unknown about the detailed combustion behavior of fuels under this novel ICE technology, such as relevant ignition temperature regimes and surrogate requirements under various engine load and speed conditions as well as for different fuels. Engine and spray simulations require the use of carefully designed surrogate fuels that mimic the properties of real fuels. Generally, these surrogates range from simple primary reference fuels (PRFs) to complex multi-component mixtures. This study aims to identify the relevant temperature conditions and the surrogate requirements for GCI engines covering the entire engine speed-load map; engine loads between 1 and 22 bar indicated mean effective pressure (IMEP) and engine speeds between 800 and 2500 revolutions per minute (RPM). Simulations were performed using the constant volume zero-dimensional (0-D) and homogeneous charge compression ignition (HCCI) modules in Chemkin-Pro for two gasoline fuels with widely different sensitivities (11 and 0). Furthermore, homogeneous ignition delay times and Livengood-Wu integrals were used to analyze the fundamental characteristics of GCI combustion. It was found that, except at excessively high-load, the relevant ignition temperature in a GCI engine is in the 750–1000 K range. The low-temperature (less than700 K) reactivity exhibited negligible contribution to the ignition of the high-sensitivity fuel. Two stage ignition and cool flame formation were found to dominate mid-load kinetics of the low-sensitivity fuel. Simple PRF surrogate was found to be sufficient to mimic the ignition requirement of the low-sensitivity gasoline fuel at almost the entire GCI engine speed-load map. However, for the high-sensitivity gasoline fuel, TPRF and TPRFE surrogates were needed for a better representation of the auto-ignition behavior. The obtained knowledge of the surrogate requirement and the ignition temperature regimes inside GCI engine will aid in guiding GCI engine optimization and fuel design.